Serapi Corner / Abdul Haadi Nur Abdul Razak … [et al.]. - Abdul Razak, Abdul Haadi Nur; Henery, Esmiesha; Mohamad Rosli, Ieffa Rozlin; Bakeri, Iffah Marwati; Samsu, Shahmy Haziq (2019)
Serapi Corner is known as one of the best restaurant in Kuching. Known for their delicious cuisine and variety of foods, its delicacies have never to disappoint the diners. This is the reason why we chose Serapi Corner; this is due to their expertise in managing a big restaurant such as that. We decided to pick Serapi Corner to become our case study because we want to learn the way they managing and tackling certain problems of their business. Some of the problem can be identified which is financial problem, employees or in other word team management and also competition.